An Investigation into Performance Appraisal System as an Effective Tool for Motivation (Global Journal of Management and Business Research, 2020)
Background of the Study- Managers and staff often dread performance appraisal like the plague but -done correctly #x2013;they can actually be enjoyable and productive for both parties. Performance appraisal is perceived to be a critical human resource management function in most organisations. In the United States of America, research estimates that over 90%
Keywords: performance appraisal; career planning; effective work; organisational goals